Adolescents' loneliness in European schools: a multilevel exploration of school environment and individual factors - Sylke V. Schnepf; Michela Boldrini; Zsuzsa Blaskó (BMC, 2023)
Abstract Background Loneliness has been recognized as a public health issue and has moved into a number of European countries' policy agendas. Literature examining loneliness in young people (and especially in adolescents) is scarce, but it does show that at this age feelings of loneliness have been increasing in recent decades and are detrimental for both adolescents' current and future well-being. In order to explain loneliness, current literature focuses generally on individual, rather than on broader, environmental characteristics. This study examines school associates of loneliness and compares their importance to those at the individual level because schools are the most important places in which adolescents are socially embedded. In addition, policy interventions on loneliness might be more feasible at the school than the individual level. Methods This study uses a single-item measure of adolescents' loneliness feelings in schools and exploits rich data from the Programme for International Student Assessment (PISA 2018) on 23 European countries covering 118,698 students (50.2% female) in 4,819 schools. This study applies multi-level models to investigate school level factors jointly with those at the individual level. Results Differences between European schools can explain a 20% variation in feelings of loneliness, thereby indicating the importance of the school environment. Furthermore, adolescents' bullying experiences and a bullying climate in school more than doubles incidences of loneliness. In addition, a cooperative climate as well as teacher support can considerably decrease school loneliness. Cross-level interactions do exist: being from a lower socioeconomic background for instance, while not important generally, increases loneliness feelings if most of the school peers are from a better socioeconomic background. School factors appear to be more important for explaining young people's loneliness incidence than individual characteristics. Conclusion This is the first study to compare school level and individual level factors relating to youth loneliness in schools throughout Europe. Results emphasizing the importance of school environment for explaining adolescents' loneliness suggest that school level initiatives may be most appropriate in tackling loneliness when compared to wider and less contextualized national policies that focus on adolescents outside of school.